Analysis of the Efficiency of the Kalman-Type Correlation Algorithm for Tracking of a Small UAV in the Presence of Uncorrelated Interference - А. О. Герасименко; С. Я. Жук (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2021)
The article shows the relevance of the problem of development and analysis of algorithms for tracking small-sized UAVs according to video surveillance. A Kalman-type correlation algorithm for tracking of a small-sized UAV in the presence of spatially uncorrelated interference, which is the most common in practice, is synthesized. In the obtained algorithm, the UAV motion parameters are estimated independently along the axes of a rectangular coordinate system. Positioning accuracy analysis using the correlation algorithm, as well as the correlation algorithm for tracking UAVs based on the Kalman filter, was carried out by statistical modeling in the Matlab programming environment.